Development of dolomite-supported copper catalysts for glycerol hydrogenolysis to 1,2-propanediol - Azri, Norsahida (2021)
The strong growth of biodiesel production has led to a significant increase in glycerol, the by-product of the process. Therefore, this study focused into converting glycerol to high-value chemical which is 1,2-propanediol over heterogeneous catalyst. Metal supported catalyst was synthesized using wet impregnation method, later calcined, and subsequently reduced under 5%H2 environment. The metals investigated were copper (Cu), nickel (Ni), cobalt (Co), zink (Zn) and iron (Fe) while the supports used were dolomite (Dol), alumina (Al2O3), bentonite (Bent), montmorillonite (Mont), and talcum (Talc). Results showed that copper supported on dolomite (Cu/Dol) gave the best catalytic activity in glycerol hydrogenolysis. Henceforth, different loadings of copper on dolomite were synthesized. Cu/Dol catalyst calcined at 500 ºC and reduced at 600 ºC exhibited the highest glycerol conversion of 78.5% and 1,2-PDO selectivity of 79% at 200 ºC reaction temperature, 4 MPa H2, 10 h reaction time, 20wt% glycerol concentration, and 1 g catalyst dosage. After optimization study, it was demonstrated that the glycerol conversion and 1,2-PDO selectivity was increased with the increasing reaction temperature, hydrogen pressure, reaction time, catalyst dosage, glycerol concentration and copper metal loading up to their optimum value. The results were optimized at copper loading of 20wt%, 180 ºC reaction temperature, 2 MPa hydrogen pressure, 6 h reaction time, 20wt% glycerol concentration, and 1 g catalyst dosage with maximum glycerol conversion of 100% and 1,2-PDO selectivity of 92.2%. It can be concluded that the high performance of 20%Cu/Dol catalyst was attributed to its macroporous and crystalline features, composed of mixed crystalline phases with calcium, magnesium, oxygen as main components, good copper surface area, copper dispersion and thermal stability. Also, the good copper-dolomite interaction, including high metal reducibility (~291 ºC) and very importantly the presence of its high acid capacity (19528 μmol/g) with Lewis sites on the catalyst surface as the active reaction sites. In addition, the incorporation of copper to dolomite presented a promising reaction performance rather metallic copper and dolomite alone attributed to its improved acidity and metal reducibility. On subjecting the 20%Cu/Dol to reusability study in five reaction cycles, it maintained good performance in glycerol conversion but inferior in 1,2-PDO selectivity after the first use. The evidence indicated that the reduced 1,2-PDO selectivity was due to the coke formation and leaching of metal active sites (Cu, Ca dan Mg). The conversion of glycerol to 1,2-PDO followed the dehydration–hydrogenation pathway while reaction towards C–C cleavage with methanol as side product was minimal.